Experiencing pregnancy at an advanced maternal age in a private hospital - Andressa Kachel Chemim; Beatriz Cristina de Castro; Juliane Dias Aldrighi; Marilene Loewen Wall; Aline Lara de Carvalho; Bruna Gizele Noronha de Medeiros; Tatiane Herreira Trigueiro (Universidade Federal do Ceará, 2022)
Objective: to describe the experiences of pregnant women at advanced maternal age assisted in a private hospital. Methods: a qualitative study, carried out with 17 women, by means of semi-structured interviews via telephone. The data was submitted to Thematic Content Analysis. Results: the participants were between 35 and 40 years old. Two categories emerged: Experiencing pregnancy as a couple and family: the preparation of the couple for pregnancy and childbirth (Pregnancy after 35 years old as an element of potentiality; Change in the family routine for the baby's arrival) and Experiencing pregnancy and its changes: perceiving pregnancy as a healthy and calm experience (Change in emotional patterns related to the pregnancy process). Conclusion: experiencing pregnancy late in life was not a concern for women. Maturity and favorable socioeconomic conditions may have a protective influence on the course of healthy pregnancies in women attending the private health service.